The improved low cost grid connected EV charging station with PV and energy storage systems - Tutkun, Nedim; Zulkifli, Shamsul Aizam; Ahmad, Zarafi (2024)
Recently electric vehicles (EVs) have increasingly been used for transportation due to low cost operation and less carbon emission. However, major disadvantages of EVs are charging time, range and overloading the grid, and the latter may lead to instability in the grid when a vast number of EVs are simultaneously charged from the grid. One solution to this may be to charging times and to share amount of charging power through photovoltaic (PV) and energy storage (ES) systems with minimum cost. In this study, a 20 kW grid tied charging station with PV and ES systems is designed to charge EVs with minimum cost for the hourly changing electricity price through a variety of charge options such as grid to EV, ES to EV, PV to EV, EV to EV etc. This is achieved by optimizing charge start times and facilities using metaheuristic based computational algorithms. The proposed approach worked well and results obtained are encouraging and meaningful for the case study